Prospects of Agroforestry in the Rural Development of Arunachal Pradesh - Singh, B.; Rethy, P.; Singh, N.D. (Journal of Soil and Water Conservation, 2022)
Agroforesty/Farm forestry is an important component of development in Arunachal Pradesh. The land-use and Jliuni cultivation in the State have been described in this paper. It has been found that Agroforestry could be developed in the state for providing timber, fitel, grasses and other requirements of the area. Various models have been suggested to improve the land-use and also increase the income of the local population.